Nation Building in Southeast Asia: Conflict, Ethno-Religious Nationalism and Islamic Education in Indonesia and Thailand - Satibi, Ibi; Talib, Ahmad Tarmizi; Rohmawati, Wiwin Siti Aminah; Said, Muhammad (FIKRAH, 2022)
This article aims to describe the nation-building discourse and movement in Southeast Asia, particularly in Aceh-Indonesia and Pattani-Thailand. The significance of this research lies in the fact that these two regions share similar characteristics. Among them are socio-cultural and religio-political situations as conflict-affected areas with the dynamics of national discourse, and fluctuate views on national integration with the state. Islamic educational institutions in these two regions have contributed significantly in the formation of the nation-state. Dayah in Aceh and Pondok in Pattani not only serve as the centres of Islamic studies and character building for the community, but also function as the stage for social, cultural and political movements. Thus, Dayah and Pondok became the institutions to shape Islamic extremist as well as the agent to strengthen political identity. This article attempts to explain the genealogy of Islamic education and the metamorphosis of national discourse in these two regions. In addition, this article will also reveal the role of local actors in ethno-religious discourses and movements, and the response of the state and its apparatus in efforts to maintain national unity and statehood